PERANCANGAN SISTEM PAKAR TINGKAT PERSENTASE PENYAKIT ANOREKSIA NERVOSA MENGGUNAKAN METODE DEMPSTER SHAFER - Harianja, Eva Julia Gunawati; Napitupulu, Junika (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2020)
Anorexia Nervosa (AN) is an eating disorder by making yourself feel hungry (self-starvation). Usually occurs in young women who are stepping on the high school bench (General High School). Their goal is to make themselves hungry so that they have a slim physical appearance and attract the attention of the opposite sex. There are 2 types of Anorexia Nervosa, Restrictive Anorexia Nervosa, people with this type of anorexia greatly limit the amount of food they consume, in fact they often do not eat at all until their bodies become very thin. Anorexia Nervosa Binge-purge, this type of anorexia is almost the same as bulimia. People who suffer from this disorder will eat in large quantities. But after eating, they will tend to feel guilty and then force to vomit back the food they ate. Mahoni Mental Hospital is one of the agencies engaged in health services, as a health agency, it is a must for the agency to improve its services both in terms of speed and timeliness. Mahoni Mental Hospital does not yet have a computerized system or method used to diagnose Anorexia Nervosa. Therefore, there is often a delay in the treatment of anorexia nervosa disorders. This study aims to build an expert system that functions as a tool for the Mahogany Mental Hospital or medical (experts) and medical students in diagnosing Anorexia Nervosa disorders. This study uses the Dempster Shafer method, in diagnosing Anorexia Nervosa disorder, based on the symptoms felt by the patient, then the results of the consultation are how many percent of the patient is affected by Restrictive Anorexia Nervosa or what percentage of the patient is Anorexia Nervosa Bingepurge